Pelaksanaan Belajar Dari Rumah (BDR) selama darurat COVID-19 di kelas V sekolah dasar - Watin 'Azizah; Idam Ragil Widianto Atmojo; Joko Daryanto (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
This qualitative research was made in purpose to know the implementation of BDR (Belajar Dari Rumah) and to determine the effectiveness of BDR (Belajar Dari Rumah) in class VA SDN Mojolegi in terms of the quality of learning, of suitability of learning level, of incentives, and of time. Data collection techniques in this study are through interview techniques, observation, angket form and documentation. Data sources in this study are through informants in the study, which are teacher and students of class VA, the implementation process of BDR in class VA, and documents. The learning process of BDR will be effective when the learning process has all good grades of effectiveness criteria. The result of the study shows that implementation of BDR in class VA has been following the       guidelines from the Indonesian Ministry of Education. It  also shows the effectiveness of BDR learning process in class VA is still less effective and needs improvement. The effectiveness of BDR learning process in class VA is still ineffective, due to the lack of interest and motivation of students. Also the lack of inovations and continuous interaction between students and teachers in the BDR learning process which causes less effective learning process for class VA students at SDN Mojolegi Teras, Boyolali.